2011
DOI: 10.1007/s12639-011-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transmission of Babesia equi (Theileria equi) from carrier mares to foals

Abstract: This article communicates the first per-acute and fatal clinical report of transplacental transmission of Theileria equi from carrier mothers to foals from Punjab, India. Two cases of equine piroplasmosis due to T. equi were diagnosed in neonatal foals borne to Throughbred mares. High degree of parasitemia with annular and maltese cross shaped parasites in erythrocytes was seen in both cases. Blood cellular changes revealed leucopenia and neutropenia with mild degenerative left shift. Anaemia was macrocytic no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 6 publications
0
28
0
3
Order By: Relevance
“…The disease has impact on the equid industry worldwide (De Waal, 1992). In India, isolated clinical cases of T. equi have been reported (Chhabra et al 2011); along with some outbreak (Gautam and Dwivedi 1976) on the other hand, no confirmed case of B. caballi has been reported by molecular and serological methods. The clinical signs are variable and often non-specific (Bashiruddin et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease has impact on the equid industry worldwide (De Waal, 1992). In India, isolated clinical cases of T. equi have been reported (Chhabra et al 2011); along with some outbreak (Gautam and Dwivedi 1976) on the other hand, no confirmed case of B. caballi has been reported by molecular and serological methods. The clinical signs are variable and often non-specific (Bashiruddin et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It can be peracute, acute, subacute, or chronic (Rampersad et al, 2003). The peracute form is observed in neonatal foals following infection in utero, mainly in T. equi but rarely in B. caballi (Chhabra et al 2011;Sumbria et al 2014b); moreover, there is an abrupt onset of signs, which lead to collapse and sudden death. In acute case, animal suffers from fever, inappetence, gastrointestinal disturbance, swaying, depression, pale mucous membranes, or icterus, dyspnoea, anaemia and haemoglobinuria (primarily in T. equi but rare in B. caballi).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the tick vectors that have been implicated in transmission belong to the genera Dermacentor, Rhipicephalus, Amblyomma and Hyalomma (de Waal, 1992;Melhorn and Schein, 1998;Rampersad et al, 2003;Wise et al, 2013). Other viable options for transmission include iatrogenic means (Scoles et al, 2011) and transplacental transmission, reported in T. equi infections (Philips and Otter, 2004;Georges et al, 2011;Chhabra et al, 2012). Clinical presentation of overt disease is commonly associated with T. equi infections.…”
Section: Introductionmentioning
confidence: 99%
“…Neutropenia similarly has been observed in symptomatic animals with babesiosis caused by various Babesia species, 8 including cases in which there was vertical transmission of the protozoan. 9 Whether neutropenia is more common in human congenital babesiosis compared with babesiosis in infants who acquire the infection through blood transfusion is unclear, since neutrophil counts were usually not mentioned in published reports of transfusion-transmitted neonatal infection. Neutropenia has also not been mentioned in reports of babesiosis affecting older children, and our study did not include pediatric cases other than those that were acquired in utero or intrapartum.…”
Section: Discussionmentioning
confidence: 99%